Hubungan Forgiveness dengan Subjective Well-Being pada Remaja di Panti Asuhan - Eka Septarianda; Mohammad Nursalim Malay; Khoiriyah Ulfah (JURNAL PSIKOLOGI MALAHAYATI, 2020)
RELATIONSHIP BETWEEN FORGIVENESS AND SUBJECTIVE WELL BEING AMONG ORPHANAGE ADOLESCENTSThis study aims to determine the relationship between forgiveness and subjective well-being in adolescents who are in the orphanage, through the three components contained in it, i.e. life satisfaction, positive affect and negative affect. The subjects of this study were 58 adolescents in the Budi Mulya Muhammadiyah Sukarame orphanage. Data collection method using three scales, those are Heartland Forgiveness Scale (HFS), Satisfaction with Life Scale (SWLS) and Possitive and Negative Affect Schedule (PANAS). The data analysis technique used is the product moment correlation. The results of the analysis of this study explain that there is a positive relationship between forgiveness and subjective well-being through the three components in SWB. The results of this study have implications about the importance of forgiveness in increasing subjective well being in orphanage adolescent.Penelitian ini bertujuan untuk mengetahui hubungan forgiveness dengan subjective well-being pada remaja yang berada di panti asuhan, melalui tiga komponen yang terdapat di dalamnya, yaitu life satisfaction, positive affect dan negative affect. Subjek penelitian ini adalah 58 remaja panti asuhan Budi Mulya Muhammadiyah Sukarame. Metode pengumpulan data menggunakan tiga skala, yaitu Heartland Forgiveness Scale (HFS), Satisfaction with Life Scale (SWLS) dan Possitive and Negative Affect Schedule (PANAS). Data dianalisis dengan korelasi product moment. Hasil penelitian ini menerangkan bahwa terdapat hubungan yang positif antara forgiveness dengan subjective well-being melalui tiga komponen dalam SWB. Hasil penelitian ini memberi implikasi tentang pentingnya forgiveness dalam meningkatkan subjective well being pada remaja dipanti asuhan.